Multi-strategic RNA-seq analysis reveals a high-resolution transcriptional landscape in cotton - Kun Wang (Nature Portfolio, 2019)
In-depth functional characterization of genomes relies on comprehensive transcriptome data. Here, the authors employ four complementary RNA sequencing technologies to explore the transcription landscape across 16 tissues or different organ types in diploid A genome cotton using a newly developed computational pipeline.